Root and tuber crops in Barbados - Brereton, L. (International Center for Tropical Agriculture, 1986)
The situation of root and tuber crops, especially taro, cassava, yam, sweet potato, and potato, in Barbados is discussed and analyzed. Although the production and exportation of yam and sweet potato decreased during the period 1970-84, cassava and taro production, for local consumption, has remained constant. Potato, with the highest consumption, has to be imported. Aspects on cultivation, marketing, and production of these crops are briefly described. Quarantine regulations, past and present government policies, and research, training, and technological development of these crops are indicated. The importance of a credible data base with statistics of root and tuber crops is highlighted. (CIAT)